2018
DOI: 10.3892/mmr.2018.9259
|View full text |Cite
|
Sign up to set email alerts
|

MiR‑500a‑5p promotes glioblastoma cell proliferation, migration and invasion by targeting chromodomain helicase DNA binding protein 5

Abstract: Glioblastoma is one of the most common malignant primary tumors and develops in brain. The molecular mechanism that regulates glioblastoma occurrence still remains unknown. MicroRNA (miR)-500a-5p has been reported to be involved in hepatocellular carcinoma and breast cancer. Whether miR-500a-5p regulates glioblastoma progression requires further investigation. In the present study, miR-500a-5p was highly expressed in malignant glioblastoma tissues and cell lines. Overexpression of miR-500a-5p promoted glioblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The results indicated that the lncRNA NEAT1 might suppress the development of gastric cancer by promoting gastric cancer cell apoptosis. Previous studies have identified miR-500a-3p as a potential prognostic predictor in certain types of cancer, including hepatocellular carcinoma and glioblastoma, and have reported an association between miR-500a and TNM stage in lung cancer and conjunctival malignant melanoma (32)(33)(34)(35). Other studies have reported that XBP-1 is closely associated with clinical outcome (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the lncRNA NEAT1 might suppress the development of gastric cancer by promoting gastric cancer cell apoptosis. Previous studies have identified miR-500a-3p as a potential prognostic predictor in certain types of cancer, including hepatocellular carcinoma and glioblastoma, and have reported an association between miR-500a and TNM stage in lung cancer and conjunctival malignant melanoma (32)(33)(34)(35). Other studies have reported that XBP-1 is closely associated with clinical outcome (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that miR‐500a‐5p was decreased in MN tissues. CXCL16 has been reported to be increased in patients with chronic kidney diseases 13 . Subsequently, the expression of CXCL16 was also examined in MN tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that miR‐500a‐5p inhibits cell growth in human colorectal cancer 12 . In glioblastoma, miR‐500a‐5p enhances cell proliferation and metastasis, 13 whereas the role of miR‐500a‐5p in podocyte apoptosis and whether miR‐500a‐5p participates in circ_0000524‐mediated function need be further addressed. The upregulation of C‐X‐C chemokine ligand 16 (CXCL16) is related to the development of chronic kidney disease 14 .…”
Section: Introductionmentioning
confidence: 99%
“…21 Xia et al 22 have confirmed that miR-1908 could facilitate cell proliferation and migration by suppressing PTEN tumor suppressor pathway in GBM. Liu et al 23 have reported that miR-500a-5p could accelerate the proliferation, migration and invasion through targeting chromodomain helicase DNA binding protein 5 in GBM.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Xia et al 22 have confirmed that miR-1908 could facilitate cell proliferation and migration by suppressing PTEN tumor suppressor pathway in GBM. Liu et al 23 have reported that miR-500a-5p could accelerate the proliferation, migration and invasion through targeting chromodomain helicase DNA binding protein 5 in GBM. In this study, we demonstrated that miR-6071 could significantly suppress proliferation, migration and invasion, and also facilitate apoptosis in U251 and A172 cells.…”
Section: Discussionmentioning
confidence: 99%